Evaluation of the InterRAI Early Years for Degree of Preterm Birth and Gross Motor Delay - Iantosca, Jo Ann M.; Stewart, Shannon L. (Frontiers in Psychology, 2022)
Background. The interRAI 0-3 Early Years was recently developed to support intervention efforts based on the needs of young children and their families. One aspect of child development assessed by the Early Years instrument are motor skills, which are integral for the maturity of cognition, language, social-emotional and other developmental outcomes. Gross motor development, however, is negatively impacted by pre-term birth and low birth weight. For the purpose of known-groups validation, an at-risk sample of preterm children using the interRAI 0-3 Early Years was included to examine correlates of preterm risk and the degree of gross motor delay. Methods. Participant data included children and families (n = 591) from 17 health agencies in Ontario, Canada. Data were collected as part of a pilot study using the full interRAI 0-3 Early Years assessment. Correlational analyses were used to determine relationships between prenatal risk and preterm birth and bivariate analyses examined successful and failed performance of at-risk children on gross motor items. A Kruskal-Wallis test was used to determine the mean difference in gross motor scores for children born at various weeks gestation. Results. Correlational analysis indicated that prenatal and perinatal factors such as maternal nicotine use during pregnancy did not have significant influence over gross motor achievement for the full sample, however, gross motor scores were lower for children born pre-term or low birth weight based on bivariate analysis. Gross motor scores decreased from 40 weeks’ gestation (mean rank = 310.77), to moderate to late preterm (mean rank = 258.96), and to very preterm (mean rank = 234.54), however extremely preterm (mean rank = 236.28) performed comparably to very preterm. Interpretation. The interRAI 0-3 was evaluated to determine its efficacy and report findings which confirm the literature regarding delay in gross motor performance for preterm children. Findings confirm that pre-term and low birth weight children are at greater risk for motor delay via the interRAI 0-3 Early Years gross motor domain.